Selective intubation with endotracheal tube introducer in difficult airway: A randomized, prospective, cross-over study - Hakan Ozerol; Emre Şancı; Onur Karakayalı; Erdem Aydın; Hüseyin Cahit Halhallı (Turkish Journal of Emergency Medicine, 2021)
BACKGROUND: Selective lung intubation is a life-saving procedure in emergency departments. While various equipment can be used in selective lung intubation, most of this equipment is not readily available; therefore, single-lumen endotracheal intubations are performed for rapid interventions.MATERIALS AND METHODS: This study was designed as a randomized, prospective, cross-over study using the 90° rotation technique for selective intubation on a manikin model with and without endotracheal tube introducer (ETI) in difficult airway settings. Forty-six emergency physicians were included in the study. The primary outcome was evaluating time to selective intubations, and secondary outcomes were first and second attempt success rates and the self-perceived difficulty level of each method according to the participants.RESULTS: The mean time to the first successful endotracheal intubation was significantly longer for both right selective and left selective intubations with ETI utilization than without ([39.71 ± 9.83 vs. 21.86 ± 5.94 s], [P < 0.001]), ([42.2 ± 10.81 vs. 26.23 ± 7.97 s], [P < 0.001], respectively). The first-pass success rate did not differ for right selective intubation with or without an ETI (45/46 [97.8%] and 45/46 [97.8%], respectively). However, the first-pass success rate for left selective intubation was significantly higher with ETI as compared to without an ETI (30/46 [65.2%] and 13/46 [28.3%], respectively) (P < 0.001).CONCLUSIONS: While the success rates of right selective intubation were the same, the left selective intubation success rates with ETI are higher than the styletted endotracheal tube, which can be strong evidence for this method's applicability in practice. Expanding the use of ETI and increasing the experience of the practitioners can contribute to further success.